Organotypic vibrosections from whole brain adult Alzheimer mice (overexpressing amyloid-precursor-protein with the Swedish-Dutch-Iowa mutations) as a model to study clearance of beta-amyloid plaques - Humpel, Christian (Frontiers in Aging Neuroscience, 2015)
Alzheimer's disease is a severe neurodegenerative disorder of the brain, pathologically characterized by extracellular beta-amyloid plaques, intraneuronal Tau inclusions, inflammation, reactive glial cells, vascular pathology and neuronal cell death. The degradation and clearance of beta-amyloid plaques is an interesting therapeutic approach, and the proteases neprilysin (NEP), insulysin and matrix metalloproteinases (MMP) are of particular interest. The aim of this project was to establish and characterize a simple in vitro model to study the degrading effects of these proteases. Organoytpic brain vibrosections (120 μm thick) were sectioned from adult (9 month old) wildtype and transgenic mice (expressing amyloid precursor protein (APP) harboring the Swedish K670N/M671L, Dutch E693Q, and Iowa D694N mutations; APP_SDI) and cultured for 2 weeks. Plaques were stained by immunohistochemistry for beta-amyloid and Thioflavin S. Our data show that plaques were evident in 2 week old cultures from 9 month old transgenic mice. These plaques were surrounded by reactive GFAP+ astroglia and Iba1+ microglia. Incubation of fresh slices for 2 weeks with 1–0.1–0.01 μg/ml of NEP, insulysin, MMP-2, or MMP-9 showed that NEP, insulysin, and MMP-9 markedly degraded beta-amyloid plaques but only at the highest concentration. Our data provide for the first time a potent and powerful living brain vibrosection model containing a high number of plaques, which allows to rapidly and simply study the degradation and clearance of beta-amyloid plaques in vitro.